2013
DOI: 10.1515/jcim-2013-0001
|View full text |Cite
|
Sign up to set email alerts
|

Hericium erinaceus: an edible mushroom with medicinal values

Abstract: Mushrooms are considered as nutritionally functional foods and source of physiologically beneficial medicines. Hericium erinaceus, also known as Lion's Mane Mushroom or Hedgehog Mushroom, is an edible fungus, which has a long history of usage in traditional Chinese medicine. This mushroom is rich in some physiologically important components, especially β-glucan polysaccharides, which are responsible for anti-cancer, immuno-modulating, hypolipidemic, antioxidant and neuro-protective activities of this mushroom.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
73
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(79 citation statements)
references
References 11 publications
2
73
0
4
Order By: Relevance
“…They also have different solubilities in different chemical solvents (10). Thus, each extraction inevitably was a mixture of numerous constituents.…”
Section: Discussionmentioning
confidence: 99%
“…They also have different solubilities in different chemical solvents (10). Thus, each extraction inevitably was a mixture of numerous constituents.…”
Section: Discussionmentioning
confidence: 99%
“…The mushroom is called "Yamabushitake" and "Houtou" in Japan and China, respectively. The fruiting bodies of H. erinaceum contain several bioactive substances, including aromatic compounds, diterpenoids, steroids, and polysaccharides (Jiang et al, 2014;Khan et al, 2013;Wasser, 2014). A doubleblind, placebo-controlled study showed that oral administration of dried Yamabushitake powder to Japanese subjects is effective for the treatment of mild cognitive impairment patients (n = 15) (Mori et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…One should, however, consider that wild edible mushrooms are potentially subject to a higher contamination level than cultivated species, for which the environmental conditions can be controlled. According to our knowledge, the present study is the first report on kinetics of As uptake and accumulation by H. erinaceus, an edible mushroom species revealing therapeutic properties [31]. Importantly, the increase in total As content was observed only when cultivation was maintained at an initial metalloid concentration of over 0.2 mM.…”
Section: Discussionmentioning
confidence: 61%